De la bibliothèque au « Tesseract » : une représentation borgésienne de la littérature dans le film de Christopher Nolan Interstellar (2014) - Emmanuel Buzay (ReS Futurae)
The library of the character Murphy in Christopher Nolan’s film Interstellar (2014) is innovative in its staging of intertextual references, as well as integrating a four-dimensional media device: a “tesseract”. In addition to the reading paths that many of the works in this library suggest, the imaginary of mediation through books also plays an essential function in the world sketched out by this science fiction film. Because it is decisive for understanding the way in which the library, as a memory of the world, rethinks humanity, its mutations, and its limits in a journey through time, the constant represented by the figure of the “book in the film” reveals a double identity which, although based on scientific knowledge, nonetheless reactivates an immemorial imaginary with its mythologies. Such an experience—which unfolds between, on the one hand, a few hypotheses of quantum physics and, on the other hand, the imaginary of mediation by the book whose transmission qualifies our humanity—is part of the very long duration of the mythologies of the invention of writing, evoked by the reference to the work of Jorge Luis Borges, The Library of Babel. This article focuses on the key moments of the changes induced by the remediation of Murphy’s library into a “tesseract”, as well as the existential implications of such changes in the realm of fiction.